Participation Means Learning by Doing : GEF’s Experience in Biodiversity Conservation and Sustainable Use - Harstad, Jarle (World Bank, Washington, DC, 2012)
A Global Environment Facility (GEF) special study on stakeholder participation and social issues, including science and technology, was conducted for 30 GEF-financed biodiversity conservation and sustainable use projects which have been completed or are near completion. The findings indicate that the degree of stakeholder participation varies by country and project, but the most effective approaches were those designed at local or community levels.